2016
DOI: 10.1128/jb.00343-16
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Sequence Structure Requirements for Recognition and Discrimination of Target RNAs by Pseudomonas aeruginosa RsmA and RsmF

Abstract: R NA-binding proteins play an integral role in the posttranscriptional regulation of protein synthesis by altering translation initiation, mRNA stability, and/or RNA processing. The CsrA family of RNA-binding proteins regulates carbon metabolism, virulence factor production, and motility in a number of Gramnegative bacteria (1-5). CsrA proteins usually bind sites on target mRNAs that overlap the Shine-Dalgarno sequence to prevent translation initiation (6-8). Although considerable sequence variability exists b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 38 publications
7
40
0
Order By: Relevance
“…This study established that the primary RNA sequence is most important for CsrA binding, and that the presentation of the GGA motif in a loop increases the affinity of CsrA-RNA interaction. More recently, a SELEX method that exploited deep sequencing of RNAs identified a consensus for Pseudomonas aeruginosa RsmA and RsmF as CANGGAYG, with the GGA motif typically found in a hexaloop (43). This sequence and structural arrangement is remarkably similar to that determined for E. coli CsrA.…”
Section: Rna Sequence and Structural Features Of Csra Binding Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…This study established that the primary RNA sequence is most important for CsrA binding, and that the presentation of the GGA motif in a loop increases the affinity of CsrA-RNA interaction. More recently, a SELEX method that exploited deep sequencing of RNAs identified a consensus for Pseudomonas aeruginosa RsmA and RsmF as CANGGAYG, with the GGA motif typically found in a hexaloop (43). This sequence and structural arrangement is remarkably similar to that determined for E. coli CsrA.…”
Section: Rna Sequence and Structural Features Of Csra Binding Sitesmentioning
confidence: 99%
“…Crosslinking studies with purified CsrA established that E. coli CsrA functions as a homodimer (5, 43). Subsequent structural studies demonstrated that each subunit of the dimer contains five β-strands (β 1 -β 5 ), an α-helix, and a flexible C terminus (44).…”
Section: Csra and Csra-rna Structurementioning
confidence: 99%
“…We used the previously described P tssA1’-‘lacZ translational reporter as surrogate for regulatory control of T6SS (13) and P exsD-lacZ transcriptional reporter as marker for the T3SS (30). RsmA/RsmF directly bind the tssA1 leader region to inhibit translation (12, 13) and positively regulate T3SS gene expression through a mechanism that remains to be defined (13). In a mutant lacking rsmV , rsmY , and rsmZ , RsmA/RsmF availability is high resulting in repression of P tssA1’-‘lacZ reporter activity and high levels of P exsD-lacZ reporter activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RsmA and RsmF both bind to RsmV with high affinity in vitro (Fig. 3A), and the affinity of RsmF for RsmV is at least 10-fold higher than for RsmY and RsmZ (12, 13). Although the affinity of RsmF for RsmV is higher in vitro, RsmV does not seem to show preferential activity towards RsmF over RsmA in vivo (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation